Totally laparoscopic, multi-stage, restorative proctocolectomy for inflammatory bowel diseases. A prospective study on safety, efficacy and long-term results. Issue 12 (December 2018) - Sampietro, Gianluca M.; Colombo, Francesco; Frontali, Alice; Baldi, Caterina M.; Carmagnola, Stefania; Cassinotti, Andrea; Dell'Era, Alessandra; Massari, Alessandro; Molteni, Paola; Dilillo, Dario; Fociani, Paolo; Tonolini, Massimo; et al.
Abstract: Background: Laparoscopic ileo-pouch-anal anastomosis (IPAA) has been reported as having low morbidity and several advantages. Aims: To evaluate safety, efficacy and long-term results of laparoscopic IPAA, performed in elective or emergency settings, in consecutive unselected IBD patients. Methods: All the patients received totally laparoscopic 2-stage (proctocolectomy and IPAA – stoma closure) or 3-stage (colectomy – proctectomy and IPAA – stoma closure) procedure according to their presentation. Results: From July 2007 to July 2016, 160 patients entered the study. 50.6% underwent a 3-stage procedure and 49.4% a 2-stage procedure. Mortality and morbidity were 0.6% and 24.6%. Conversion rate was 3.75%. 8.7% septic complications were associated with steroids and Infliximab treatment (p = 0.0001). 3-stage patients were younger (p = 0.0001), with shorter disease duration (p = 0.0001), minor ASA scores of 2 and 3 (p = 0.0007), lower inflammatory index and better nutritional status (p = 0.003 and 0.0001), fewer Clavien-Dindo's grade II complications (p = .0001), reduced rates of readmission and reoperation at 90 days (p = 0.03), and shorter hospitalization (p = .0001), but with similar pouch and IPAA leakage, compared to 2-stage patients. 8 years pouch failure and definitive ileostomy were 5.1% and 3.7%. Conclusion: A totally laparoscopic approach is safe and feasible, with very low mortality and morbidity rates and very low conversion rate, even in multi-stage procedures and high-risk patients.